Facile synthesis of molybdenum multisulfide composite nanorod arrays from single-source precursor for photoelectrochemical hydrogen generation - Lim, C.E. (Springer Nature, 2019)
Abstract: The deposition of molybdenum multisulfide thin-film photoanodes from the metalâorganic precursor CpMo(SMe)22 (1), at different deposition time has been investigated. Four different films were deposited at 550Â Â°C under constant argon gas flow for 10, 15, 20, and 25Â min, respectively. The surface morphology of these films analyzed with FE-SEM and AFM showed the presence of compact 1D rod-like structure of MoS2/Mo2S3in a homogeneous form. The average diameter of the 1D compact MoS2/Mo2S3 composite nanorod arrays was found in the range of 155â298Â nm deposited for different time durations. EDX analysis showed a consistency where the Mo-to-S ratio was approximately 3:4.5 and demonstrated the overall composition of the 1D MoS2/Mo2S3 composite nanorod arrays. The XRD analysis of the thin film indicated the presence of monoclinic Mo2S3 and rhombohedral MoS2composite system. Moreover, the photocurrent density of 20Â min deposited thin film is observed to be 4Â mA/cm2 with highest photosensitivity of 6.78Â at the overpotential of 0.3Â V vs Ag/AgCl under the simulated light intensity of 100Â mW/cm2 (AM 1.5G). The electrochemical impedance spectroscopy (EIS) also showed improved charge transportation with highest lifetime of the photoexcited charges in 20Â min deposited thin film in comparison to the other deposition time durations. This study provides the optimized synthesis conditions for producing molybdenum-based multisulfide nanostructures and the deposition duration for their deployment in solar-based devices. Graphical abstract: Complex CpMo(SMe)22 (1) has been used as a single source precursor for fabrication of MoS2/Mo2S3 composite nanorod arrays on FTO glass substrate and tested for photoelectrochemical hydrogen generation. Figure not available: see fulltext.. Â© 2019, King Abdulaziz City for Science and Technology.